Better olfaction was associated with lower healthcare expenditure among physically independent Japanese community-dwelling older adults: the Yanai study - Kose, Yujiro; Hatamoto, Yoichi; Tomiga-Takae, Rie; Kimuro, Yukari; Aoyagi, Ryo; Kawasaki, Hikaru; Komiyama, Takaaki; Ichikawa, Mamiko; Fujiyama, Katsutoyo; Murata, Yoshiro; Ikenaga, Masahiro; Higaki, Yasuki (Frontiers in Aging, 2025)
ObjectiveWe aimed to determine whether olfaction is associated with healthcare expenditure among physically independent, community-dwelling older adults.MethodsThis cross-sectional study included 162 community-dwelling older adults (mean age 70.2 ± 5.4 years; 48 men and 114 women) from the 2015 Yanai Study. Of these, we followed 71 participants (mean age 70.0 ± 5.7 years; 26 men and 45 women) in a longitudinal pilot study over 1.5 years, which measured healthcare expenditure from May 2015 to October 2016. Olfaction was examined using the Odor Stick Identification Test for Japanese people.ResultsThe cross-sectional analysis showed that better overall olfaction was significantly associated with lower orthopedic expenditure at baseline when adjusted for covariates (f = 2.19; p = 0.115; p for linear trend = 0.048). This association remained significant in the model adjusted for final covariates (f = 2.30; p = 0.105; p for linear trend = 0.034). Better olfaction scores (≥8) were associated with lower orthopedic expenditure in the final covariate model [odds ratio (OR): 0.780; 95% confidence interval (CI): 0.612–0.994; p = 0.045]. The longitudinal analysis showed that a baseline olfaction score ≥8 was associated with lower total healthcare expenditure, outpatient visit expenditure, and internal medicine expenditure, independent of covariates over 1.5 years, in the model adjusted for final covariates (group × time interaction: f = 4.05, p = 0.021; f = 4.34, p = 0.016; and f = 6.20, p = 0.005).ConclusionBoth the cross-sectional and longitudinal analyses suggested that better olfaction ability is associated with lower healthcare expenditure. These results may help increase awareness of olfactory dysfunction at an earlier stage among physically independent, community-dwelling older adults.